A Physical Model for Interseismic Erosion of Locked Fault Asperities. Issue 10 (7th October 2017) - Mavrommatis, Andreas P.; Segall, Paul; Johnson, Kaj M.
Abstract: The conventional "asperity model" posits that faults are partitioned into fixed velocity‐weakening (VW) patches (asperities) that are locked interseismically and velocity‐strengthening (VS) regions that creep stably without accumulating stress. However, studies of GPS‐derived deformation in northern Japan have shown that interseismic strain in the Tohoku region did not accumulate at a constant rate (as expected) but gradually decreased from 1996 to 2011. This change in strain rate is consistent with locked asperities shrinking by ∼75% in area during this period. Here we consider a modification to the conventional asperity model, such that thermal pressurization (TP) is active over an area that encompasses a VW region and part of the surrounding VS region. In our quasi‐dynamic simulations, TP causes shear stress during rapid slip to decrease to very low levels. During the interseismic period, stress gradually recovers to steady state friction at the plate rate, at which point stable creep initiates. The creep front propagates inward, effectively eroding the locked asperity. For uniform properties, the locked area shrinks roughly linearly in time through the VS region. Locked asperities shrink more slowly with higher nominal friction coefficient or background effective normal stress in the VS region, lower hydraulic diffusivity, and larger TP zones. Lateral heterogeneity in properties can give rise to nonlinear erosion. Predictions from this model can be compared against GPS data to test whether the model can explain the observed changes in interseismic strain rate in Tohoku. Key Points: A physical model for locked fault asperities that shrink during the interseismic period is developed Numerical simulations of rate‐and‐state friction with thermal pressurization show that locked area shrinks roughly linearly over time We investigate the rate of asperity erosion as a function of fault strength, hydraulic properties, and asperity size